Afterglow - Tupper, Angie Lea (UnderCurrents: Journal of Critical Environmental Studies, 2022)
You can see Afterglow in motion at https://tiny.cc/uc_afterglow or https://youtu.be/kjKQr38c7qA. This mixed media piece explores the relationship between memory and home videos. The chosen scene is an everyday glimpse of childhood recreation: my cousins and I swivel in the sand at the water’s edge. I have a distinct memory of the sunshine wicking water droplets from my skin with its radiant warmth, but when I return to re-watch the home video, the light projecting from the screen is an undeniably overcast grey. Even with this discrepancy between my body memory and the recording, I question how much my recollection is a testimony of the immediate sensory experience and how much it is an adaptation of the home video that I have seen replayed so many times. It is one of few recordings that capture my cousin Oliver and me together; 2022 marks the fourteen-year anniversary of his death. The light that bounced off of our forms, that summer afternoon, is re-animated with each replaying of the video. Memory is re-minded with each re-watching. My process developed as a response to this shifting palimpsest of recollection. After transferring twelve evenly-spaced video frames to canvas, I hand-painted and beaded the degraded stills to match the coloration of my mind’s image. In their final iteration, the canvases are presented in sequence as a lenticular print. Moving in tandem with the viewer, the effect mirrors the physicality of body memory. Each retouched frame can only be viewed in a fugitive moment. The sequence provokes the viewer to waltz around the scene, back and forth, through impressions of time. In contrast, the vertical plastic lenses of the lenticular print recall the striations of traditional televisions. Painterly textures and interactive motion compete with an impression of flatness and locked recording. It is false to say that the screen is incapable of putting us ‘in the presence of’ the actor. It does so in the same way as a mirror . . . but it is a mirror with a delayed reflection, the tin foil of which retains the image. (Bazin 97)